OPTIMALISASI PHOTOGRAMMETRY TEKNIK QUALITY OF CAMERA PADA VISUALISASI MODEL 3D - Ibnu Hadi Purwanto; Suyanto Suyanto; Sukoco Sukoco (Informasi Interaktif, 2017)
The development of increasingly advanced visualization of 3D models. One method of visualization model 3 that is using close range photogrammetry. Starting from the number of digital cameras with high resolution, the authors are interested in doing research on optimization photgrammetry using techniques quality of the camera on a 3D model visualization. The purpose of this research is to optimize the quality of the camera for 3D models pembutan particular model of a human head. In per cent of research using methods of research and development. The results show to get a good result in this photogrammetry photograph obtained configuration beetwen 65 ° angle and the image is taken every 15 ° with setting shutter speed 1/60, aperture 6.3 and ISO 400. For taking pictures made outdoors when the weather is right - Right flat, in the sense not too dark and not too light. This is to anticipate the object is in backlight conditions. The impact of the quality of camera is very influential on the visualization of 3D shapes generated. If the quality of the camera is not guaranteed, the results visualization 3d models using close range photogrammetry method will not be formed. Less appropriate camera settings can cause picture to become unfocused, under exposure and over exposure. Objects to be imperfect and there is a hole or a hole issue. Over exposure can also cause a hole in the object. While under exposure will cause intersection on the object.Keyword: Photogrammetry, researh and development, quality of camera